KAJIAN ESTETIKA DAN NILAI PENDIDIKAN TARI SEKAPOR SIREH DI SANGGAR BOUGENVILLE KALIMANTAN BARAT - Faisal, Romi; Slamet Haryono; Muhammad Ibnan Syarif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research explores the aesthetic values and education values of the “Sekapor Sireh” dance as practiced at Sanggar Bougenville in West Kalimantan. As a traditional welcoming dance of the Malay community in Pontianak, the “Sekapor Sireh” dance represents symbols and meanings that reflect the cultural character of the people of West Kalimantan. More than just an aesthetic expression, the dance also carries educational values that develop both in its performance and throughout the learning process. These values play an essential role in shaping the character of the younger generation. This study applied a qualitative method with a case study design., data were collected through observation, interviews, and documentation involving studio administrators, dance instructors, senior and junior dancers, as well as cultural figures. The findings reveal that the aesthetic dimensions of the “Sekapor Sireh” dance can be examined through this approach, content, and performance, all of which are harmoniously combined into a single artistic expression. The educational values represented in the dance such as gentleness, politeness, respect, and tolerance reflect the character of the local community and are further strengthened through the training process, which nurtures discipline, cooperation, and cultural appreciation among young learners. Overall, the “Sekapor Sireh” dance serves not only as a ceremonial art for welcoming guests but also as a significant medium for cultural transmission and character education. It contributes to preserving cultural heritage while supporting the moral and personal development of the younger generation.